РЕЗУЛЬТАТЫ МОНИТОРИНГА ЗООПЛАНКТОНА СЕВЕРНОГО КАСПИЯ В УСЛОВИЯХ СЕЙСМОРАЗВЕДКИ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
Effect of seismic survey on zooplankton resulting caused by engineering and geological prospecting in the North-East part of the Caspian Sea were researched (from 2 to 4 meters deep). The zooplankton was collected with the Juday net in July — August 2011 at 5 stations in three replications: baseline, during the seismic survey and 24 hours thereafter. In baseline studies the wind force did not exceed 3.5 m per sec., subsequently it rose up to 7-8 m per sec. Widespread were rotifera Brachionus quadridentatus hyphalmyros, B.plicatilis rotundiformis, cladocera Podonevadne trigona andP. camptonyx, copepoda Acartia tonsa, cirripedia nauplii and polychaeta larvae. At one of the five stations the plankton counts in the baseline studies were equal to the plankton counts in the seismic survey, with almost complete absence of damaged species and low wind force. At the three stations the plankton counts and weight increased from 2 to 11 times in the phase of earthquake effect and strong wind. At one station only during the seismic survey a three-fourfold decrease in the number of community species was identified, which significantly increased in the subsequent period, when there was a strong wind as well. On an average for the study areа, diversity and number of the animals increased during the seismic survey and thereafter (202 and 172 thousand specimens per m3) as compared to those in the baseline studies (113 thousand specimens per m3). In the last two periods sensitivity of invertebrate animals was a shade higher as well (3.2 - 3.7%) as compared to that in the baseline studies (1.5%), but the percent of such species did not exceed a known level of natural distortion (5-6% of the weight). Indicators off — saprobic zone and saprobity indices allowed to unambiguously characterize a water column as moderately contaminated at all stages. The plankton dynamics identified was caused by a more intensive wind activity during the last two periods and water mass transport from usual aggregated zooplankton. This type of observations did not identify any relation between the zooplankton dynamics indices and the effect of earth shocks.